EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA - Nurainun Hasibuan (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
This study aims to describe effectiveness of using cooperative learning model of TAI (Team Assisted Individualization) type on students’ mathematical communication ability at the seventh grade students of SMP Negeri 3 Padangsidimpuan. The research was conducted by using descriptive quantitative method with 40 students as the sample and they were taken by using random sampling technique from 262 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using TAI type was 3.61 (very good category) and b) the average of students’ mathematical communication ability before using TAI type was 50.45 (fair category) and after using TAI type was 83.85 (very good category). Furthermore, based on inferential statistic by using N-Gain, the result showed G = 0.67 (average category). It means, using cooperative learning model of TAI type was effective on students’ mathematical communication ability at the seventh grade students of SMP Negeri 3 Padangsidimpuan. Keywords: effective, TAI type, mathematical communication ability